Royal Blue: The Culture of Construction Workers - Gartrell, Beverley (Labour / Le Travail, 1985)
This article reviews the book, "Royal Blue: The Culture of Construction Workers," by Herbert A. Applebaum.
Keywords: APPLEBAUM, Herbert A.; CONSTRUCTION workers; Nonfiction; REVIEWS; ROYAL Blue: The Culture of Construction Workers (Book); books